Three years clinical assessment of low concentration dimethyl sulfoxide primer in non carious cervical lesions: a randomized controlled trial - Ismail, Omar Abdelaziz; Hassanein, Olfat Elsayed; Hafez, Randa; Mamdouh, Mai; Shaalan, Omar; Tezvergil-Mutluay, Arzu (ELSEVIER INC, 2025)
Objectives to evaluate the clinical effectiveness of 1% dimethyl-sulfoxide (DMSO/H2O) dentin pretreatment on the clinical performance of 2-step etch-rinse adhesive after 36-months of a follow-up.
Methods Twenty-nine patients with 82 non carious-cervical lesions NCCLs were eligible for the study. NCCLs were randomly distributed into 2 equal groups. Both groups were acid etched then bonded with (Single-bond2, 3M-ESPE) and restored with a nanohybrid composite (Z350XT, 3M-ESPE) under rubber-dam isolation. Only for the intervention group 1% DMSO/H2O was applied for 60s then blot dried after etching and before bonding. The restorations were evaluated at baseline, 12, 24-, and 36-months using FDI criteria for evaluation of the restoration. For the statistical analysis, intergroup comparison between interventions was performed using Chi-Square-test (P < .05), intragroup comparison within each intervention was performed using the Cochran's Q-test (P < .0083).
Results In the current study, intergroup comparison between both groups at baseline and after 12, 24 and 36 months showed no statistically significant differences for all tested outcomes (P > .05), except for marginal discoloration at 36 months, where there was statistically significant difference (P < .05) favoring DSMO. Intragroup comparison within control revealed statistically significant deterioration through time (P < .001) for all tested parameters, also within DSMO there was statistically significant change through time ( P < .0083).
Conclusion The clinical performance of a 2-step etch-rinse adhesive in combination with 1% DMSO pretreatment was better than the control without pretreatment. Longer follow-up and higher concentrations of DMSO pretreatmentshould be evaluated in the future. Clinical Significance Several laboratory studies showed that DMSO pretreatment improves the hybrid layer quality and integrity. However, this clinical trial gave the proof of the clinical effectiveness of this protocol after 36-months follow-up.